2008
DOI: 10.1051/forest:2008062
|View full text |Cite
|
Sign up to set email alerts
|

Variabilité de la résistance à la dégradation du bois de mélèze par les champignons

Abstract: Abstract• Decay resistance of larch (Larix sp.) to fungi was evaluated on heartwood samples belonging to 3 species (L. decidua, L. kaempferi and their hybrid), 3 races of European larch (polonica, sudetica and alpine), 13 wood lots (populations) and 313 trees.• Larch wood appeared, on average, as moderately durable although a high variability was observed. At the sample level as well as at the mean individual tree level, durability ranged from class 1 to 5 according to EN 350-1 standard. At the population leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…Many recent results support this assumption; several authors have indeed observed significant differences in extractive content and in particular in total phenolic compounds in wood of conifers between decay-resistant and susceptible trees Harju et al 2003 in Scots pine; Windeisen et al 2002 in hybrid larch; Venäläinen et al 2006 in Siberian larch). In addition, the higher decay resistance of outer heartwood compared to inner heartwood within a tree (Curnel et al 2008) can also be directly related to its higher extractives content Gierlinger and Wimmer 2004). In a coherent way, highly negative phenotypic correlations between mass loss in durability test and extractives content have been found for Scots pine (Venäläinen et al 2004) and especially for larch: by Gierlinger et al (2004b) for Larix decidua (r = -0.63 to -0.84) and for L. kaempferi (r = -0.87 to -0.88), by Windeisen et al 2002 for the hybrid L. 9 eurolepis (r = -0.77 to -0.80) and by Venäläinen et al (2006) for See description of traits codes in Table 1 Eur J Forest Res L. sibirica (r = -0.68).…”
Section: Importance Of the Heartwood Phenolic Content In Relation To mentioning
confidence: 96%
See 1 more Smart Citation
“…Many recent results support this assumption; several authors have indeed observed significant differences in extractive content and in particular in total phenolic compounds in wood of conifers between decay-resistant and susceptible trees Harju et al 2003 in Scots pine; Windeisen et al 2002 in hybrid larch; Venäläinen et al 2006 in Siberian larch). In addition, the higher decay resistance of outer heartwood compared to inner heartwood within a tree (Curnel et al 2008) can also be directly related to its higher extractives content Gierlinger and Wimmer 2004). In a coherent way, highly negative phenotypic correlations between mass loss in durability test and extractives content have been found for Scots pine (Venäläinen et al 2004) and especially for larch: by Gierlinger et al (2004b) for Larix decidua (r = -0.63 to -0.84) and for L. kaempferi (r = -0.87 to -0.88), by Windeisen et al 2002 for the hybrid L. 9 eurolepis (r = -0.77 to -0.80) and by Venäläinen et al (2006) for See description of traits codes in Table 1 Eur J Forest Res L. sibirica (r = -0.68).…”
Section: Importance Of the Heartwood Phenolic Content In Relation To mentioning
confidence: 96%
“…Indeed, larch heartwood is classified as 'moderately durable' according to European standard NF EN 350-2. A large variability has been shown between species, populations and trees within populations with wood samples ranging from 'non-durable' to 'very durable' (Gambetta et al 2004, Curnel et al 2008). In addition, a strong link was found between total extractives, in particular total phenol content, and natural wood durability (Windeisen et al 2002;Gierlinger et al 2004b;Venäläinen et al 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Besides wood quality, it seems obvious that the longevity of these constructions also relies on a high ancestral level of building expertise. Furthermore, the apparent natural durability and longevity qualities of larch wood do not seem to be expressed in the same way outside its distribution within the Alps (Curnel et al, 2008). Consequently, larch from the warmer, more fertile regions of the lowlandssometimes performs considerably worse than larch from the Alps.…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
“…Consequently, larch from the warmer, more fertile regions of the lowlandssometimes performs considerably worse than larch from the Alps. However, some of the authors reported, that durable larch wood can be found even in the lowland plantations in Eastern Europe (Curnel et al, 2008).…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
“…Wood is a remarkably naturally durable material. This natural durability in terms of decay resistance against fungi, varies in a wide range between species and even within species [78][79][80] and can also be predicted by infrared spectroscopy [78,81,82]. The natural durability of wood mainly depends on the extractives composition [79,83] but also on the extractives content [79] and is in general higher in hardwoods than in softwoods.…”
Section: Natural Durability Of Wood -Preventing Wood From Degradationmentioning
confidence: 99%